(untitled) (Revista Paradigma, 2022)
This article has as objective investigate the legal treatment applicable to the cryptocurrencies in cross borders´ financial transactions, in view of tax evasion crime. The main question is in the criminal classification, if the cryptocurrency transmitted over the internet from one country to another would subscribe the penal rule of tax evasion? To answer this question, it was necessary evaluate what cryptocurrencies are, what their legal nature is. Subsequently, it was indispensable to investigate the legal interest protected in the crime of tax evasion in the cryptocurrency operations. To solve the issue, the qualitative research methodology was adopted, as the main sources of scientific articles, doctrinal works, with bibliographic review, according to the criminal law and Information of Technology, to obtain subsidies and analysis and possible application of the crimes provided from article 22 of Law 7492/86.